PENGARUH KOMBINASI AMELIORAN PUPUK KANDANG DAN ABU SEKAM PADI TERHADAP PERTUMBUHAN DAN PRODUKSI KEDELAI (Glycine max) PADA TANAH GAMBUT - Maimunah. Intan Sari. Elfi Yenny Yusuf (Fakultas Pertanian, Program Studi Agroteknologi, 2019)
This study aims tostudy the effect of the composition of doses of chicken manure and rice husk ash on the growth and production of soybean (glycine max) on peat soils. This research was conducted in the month of February 2013 to june 2013 in the tembilahan hulu village,tembilahan hulu district,indragiri hilir regency. Initial soil analysis was carried out at the BPTP Yogyakarta Laboratory. The study used a Completely Randomized Design (CRD) with 4 treatments and 3 replications factors and 3 replications namely without treatment and treatmen of chicken manure doses in the same 3 treatments namely 2500 kg/ha, for rice husk ash using a doses of 5000 kg/ha,1000kg/ha and 1500 kg/ha, so that we can get4 cobinations off repeated 3 replications so that there ar 12 experimental units,each experimental unit consisting of 10 plant pots. The parameters observed were soil chemical properties,plant height,number of effective root nodules (100%), percentage of pithedpods,number of seeds / plants,weight of 100 seeds (grams). The data can be analyzed statiscallyif the F coutis greater than theF table followed by the tukey HSD test at the 5% level. The results showed that the combination of chicken manure and rice husk ash was significantly different from plant height and weight of 100 seeds. In the parameters of the number of effective root nodules (100%),the percentage of effective root nodules,the percentage of pithed pods,the dry weight of seeds/plants,showed no significant effect. The best weight of 100 soybean seeds is found in the combination dose of 2500 kg chicken/ha chicken manure and 1000kg/ha of rice husk ash which is 16.20g.